Use of Acoustic Camera in Rolling Stock Noise Analysis (Current Problems in Rail Vehicles, 2021)
The noise parameters of railway vehicles clearly contribute to their quality and are specifically monitored in accordance with the ever-tightening limits of TSIs or environmental regulation in general. The basis for the possibilities of reducing vehicle noise is a detailed analysis of noise sources and paths. The paper presents valuable results and new findings from acoustic experiments from the operation of trains at ŽSR using an acoustic camera.
Keywords: railway vehicles noise; acoustic camera